Epidemiological study of COVID-19 mortality in a tertiary care center of South India - Thayyil, Jayakrishnan; Padmanabhan, Aparna; Gangadharan, Alan; Annikady, Navya (International Journal Of Community Medicine And Public Health, 2022)
Background: COVID-19 infection have taken a huge death toll across the globe since its emergence in 2019 in Wuhan, China. There have been inconsistencies related to many of the epidemiological features, which vary from country to country or are not known or explained properly. Therefore, there is an urgent need to generate epidemiological evidence of COVID-19 at the state level based on the data. Also, very limited published studies from India have analyzed the factors associated with death due to COVID-19. The objective of this study was to identify the epidemiological factors involved in COVID deaths in a tertiary care center of north Kerala, South India and to compare the trend of these factors affecting COVID-19 mortality in the consecutive years. Methods: Descriptive study was conducted prospectively using secondary data extracted from the electronic surveillance records of the tertiary care center were analyzed using suitable software and presented. Results: During the study period 1747 deaths due to COVID-19 was reported. The duration of hospital stay was 6.5+ 6.3 days. The median age was 67.5 years (IQR14) and males constitute 67.5% (95% CI: 64.8-69.3%). Among them 88.3% (95% CI:86.7-89.7%) have any of reported co morbidities which mainly diabetes and hypertension. Immediate cause of mortality mainly (73.6%) ARDS. Epidemiological factors related to mortality was similar during years. Conclusions: Since COVID-19 deaths affect older age groups, and those with comorbidities, reverse isolation needs to be given more importance wherever possible and its high time to consider targeted COVID-19 vaccination among them.